2016
DOI: 10.5604/17307503.1227531
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Hemispheric Asymmetry in Fetal Alcohol Spectrum Disorders: A Review of the Effects of Prenatal Alcohol Exposure on Language Lateralization.

Abstract: SUMMARYAtypical lateralization is evident in developmental disorders, including autism spectrum disorders and dyslexia. Moreover, atypical lateralization is linked to language impairments: reduced or reversed lateralization is associated with poorer language outcomes. Fetal alcohol spectrum disorders (FASD) result from the deleterious effects of prenatal alcohol exposure on the brain, resulting in a range of physical, behaviou ral, and cognitive abnormalities, including language impair ments. To date, little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Interestingly, we observed more group differences in the left hemisphere than the right hemisphere in the present study. Cortical lateralization in white matter has not been widely studied yet in the PAE population, although a previous review found atypical asymmetry in the left temporal-parietal region associated with PAE …”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Interestingly, we observed more group differences in the left hemisphere than the right hemisphere in the present study. Cortical lateralization in white matter has not been widely studied yet in the PAE population, although a previous review found atypical asymmetry in the left temporal-parietal region associated with PAE …”
Section: Discussionmentioning
confidence: 46%
“…Cortical lateralization in white matter has not been widely studied yet in the PAE population, although a previous review found atypical asymmetry in the left temporal-parietal region associated with PAE. 57 One prior study 29 examined PAE in the full ABCD cohort and reported larger total brain volume and regional cortical volumes in the PAE group compared with unexposed controls. That study included participants who had been exposed to alcohol before awareness of pregnancy only, those with PAE reported by nonbiological parents, and children with other prenatal exposures (eg, cannabis, tobacco).…”
Section: Brain Alterations In Children With Paementioning
confidence: 99%
See 1 more Smart Citation